Carbohydrase and phytase supplementation in diets for semi-heavy laying hens - Geraldo, Adriano; Gomes, Karina Rodrigues Aurora; Fassani, Édison José; Bertechini, Antonio Gilberto; Simão, Sérgio Domingos; Nogueira, Filipe Soares (Acta Scientiarum. Animal Sciences, 2014)
This study was conducted in order to evaluate the association of phytase with an enzymatic complex comprised of carbohydrases (α-galactosidase, galactomannan, xylanase and β-glucanase) in nutrition reduction diets for semi-heavy laying hens and its effect on egg performance and egg quality. Four hundred Isa Brown laying hens with 42 to 57 weeks of age were distributed in an entirely random experiment with five treatments and 8 repetitions, during five production periods of 21 days. Variables studied: egg production, feed intake, mean egg weight, feed conversion, Haugh unit, percentage of yolk, egg white and albumen, yolk color, eggshell thickness and specific gravity. There was a significant interaction (p < 0.05) between treatments and experimental periods for feed intake. There were no significant effects (p > 0.05) of treatment on production, egg weight or internal and external egg quality. Treatment effects on feed conversion showed better values for hens fed with the control diet. The levels of nutrient reduction used in the diets with or without enzyme supplementation did not provide good results with regard to feed conversion and feed intake. However, they did not affect the other parameters for egg production and internal and external egg quality.